Sculpture as objects : 1915-1995. - Baum, Timothy; Curt Marcus Gallery, New York (New York : Nadada Editions, 1995)
Acconci, Vito ; Beuys, Joseph ; Bourgeois, Louise ; Bravo, Claudio ; Breton, André ; Broodthaers, Marcel ; Calder, Alexander ; Connor, Bruce ; Connor, Maureen ; Cornell, Joseph ; Duchamp, Marcel ; Ernst, Max ; François, Michel ; Giacometti, Diego ; Gober, Robert ; Hesse, Eva ; Horn, Rebecca ; Huszar, Vilmos ; Jean, Marcel ; Lennon, John ; Lipski, Donald ; Magritte, René ; Man Ray ; Mapplethorpe, Robert ; Oldenburg, Claes ; Oppenheim, Meret ; Pettibone, Richard ; Samaras, Lucas ; Schwitters, Kurt ; Shaver, Nancy ; Warhol, Andy
Sculpture as objects : 1915-1995, Curt Marcus Gallery, New York, in association with Timothy Baum, 28 april - 28 May 1995
Engels
kunstcatalogus